Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico - Mound, Laurence; Goldarazena, Arturo; Lopez-Guillen, Guillermo; Hance, Thierry (Zootaxa, 2016)
There are nearly 280 species of Liothrips listed from around the world (ThripsWiki 2016), all of them presumably feeding and breeding on the leaves of higher plants, and sometimes inducing or being associated with galls (Mound 1994). Despite this, for most of these species the identity of the plant species on which they are dependent is rarely known, and a particularly high proportion of the species are based on few specimens or even single individuals (cf Table 1). As a result, the identity of many of these named species continues to be in doubt. Modern identification keys are available only to the 23 Liothrips species known from Japan (Okajima 2006), the four European species known from Iran (Minaei & Mound 2014), and 14 species from Illinois (Stannard 1968). In contrast, the keys to 16 species of Liothrips from Brazil (Moulton 1933), to more than 80 species from Indonesia (Priesner 1968), and to 50 species from India (Ananthakrishnan & Sen 1980), are of little more than archival interest, in that they are based on few specimens with little allowance for intraspecific variation. Mound & Marullo (1996) listed over 80 Liothrips species from the Americas, although some of these are now placed in Pseudophilothrips (see Mound et al. 2010). That list included two homonyms of the Indonesian species Liothrips brevitubus Karny, one from Mexico and one from California. The homonym from Mexico is here recognised as applying to a species that in 2015 caused severe damage to a crop of Jatropha curcas in Chiapas. The objectives here are to provide a valid name for this pest, to facilitate its recognition among the 13 species of Liothrips recorded from Mexico (Table I), and also to replace the homonym from California.